Kinetic responses during landings of plyometric exercises - Jensen, R. L.; Flanagan, E. P.; Jensen, N. L.; Ebben, W. P. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The objective of the current study was to compare landing impulse and peak ground reaction force (GRF) during a variety of plyometric exercises. Eight Division-I athletes who routinely trained plyometric exercises performed a single repetition each of countermovement jump (CMJ), drop jumps from 30 and 60 cm (DJ30 and DJ60), cone hop (CH), tuck jump (TJ), single leg CMJ (SLJ), and squat jump with 30% 1 RM dumbbell squat (SJ30). Landing impulses and peak GRF were evaluated on an AMTI force plate. One-way ANOVA indicated mean and total impulses and peak GRF differed across exercises (p<0.05), with CH and SLJ displaying lower values and DJ30 and SJ30 having higher values. Results indicate that when landing from various plyometric exercises landing impulses and GRF are different across the exercises.